Intercultural Communicative Competence: L2 Learners’ Participation on Debating Class - Muliani, Muliani; Sumarsono, Dedi (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
Taboos in conversations will take place between speaker and hearer as the cultural awareness of the target language culture is not taken into account in the teaching and learning processes of English triggered this research to be conducted. This research deals with an analysis of intercultural communicative competence of L2 learners by means of applying Constructivists Model in which the preliminary description of how competent they are on L2 culture can be described. This research is qualitative research where eight students were arranged in debating class involved as the subject. Two debaters from Executive English Debate Community were engaged in this research as the team to construct the activities for the students. By providing anobservation checklist and questionnaire, the finding shows that the students actively exchange their ideas, they feel part of learning, they are able to develop problem-solving through peer collaboration, and they are able to develop new skills and knowledge from the other members of groups. It can be noted that the motions provided during the research, in which the L2 culture is considered, have helped the L2 learners to enhance their intercultural communicative competence seen from their active participation.